Study on Nutrient Components of Different Peanut Varieties in Different Producing Areas in Guangdong Province - Jing GUO; Bailiang ZHANG; Jiahao WANG; Gaoquan HUANG; Xiaofang ZENG; Weidong BAI; Yongping XIE; Juan YANG (Shipin gongye ke-ji, 2022)
In this study, by measuring the nutrient components of peanuts, the results of six different varieties Shanyouhong 3, Shanyouhong 4, Zhanyou 75, Shanyou 121, Shanyouhei 620, Shanyouhei 1 were analyzed and compared. The results showed that the sphericity of peanuts basically reached more than 50%, the water content was more than 5%, the fat was more than 40%, the total sugar was more than 5%, the protein was more than 20%, and the mineral content was more than 2%; the content of total unsaturated fatty acid was more than 70%, the essential amino acids reached more than 16%. In addition, the proportion of nutrients obtained by the same variety of peanuts after planting in different regions was different. For example, the fat content of Shanyou 121 in Guangzhou was 55.64%, while that in Yangjiang, Zhanjiang and Shaoguan was 52.18%, 44.86% and 49.81%, respectively. However, different varieties in the same area also had great differences. For example, in Yangjiang area, the fat content of Shanyouhong 4 was the highest of 54.35%, while the lowest of Shanyouhei 1 was only 49.95%. The analysis of peanut allergenic protein content showed that in four different regions of Guangdong, Zhanyou 75 in Zhanjiang area had the most allergenic protein content of Ara h3, and the content of Ara h2 allergenic protein in Yangjiang area was less, and there was no significant difference in other areas. The research on the nutritional components of different varieties in different regions provides a certain basis for the follow-up research on peanuts in Guangdong Province.